Exploring the potential role of educational developers in facilitating curriculum review processes - Derek Thurber; Karen Bossen (To Improve the Academy)
Despite its many benefits, curriculum review has yet to become a widespread practice in many areas of higher education. Previous research suggests that this is because of a lack of faculty time and expertise to conduct curriculum reviews independently. As such, this action research study builds on the existing literature to explore the utility of educational developers at a large research university in developing faculty communities of practice around the continuous improvement of their curriculum by facilitating a curriculum review process. The findings suggest opportunities for educational developers to partner with faculty to support this substantial work.